Penguatan usaha kelompok peternak pelaku integrasi sawit-sapi berbasis limbah di Kecamatan Mestong - Ardi Novra; Adriani Adriani; Suparjo Suparjo; Nelson Nelson; Sri Novianti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
This strengthening waste-based palm oil-cattle integration groups business program is a continuation of the development program in the 2013. It is intended to accelerate and increase production capacity through process technology improvements. The results of the activity show that the group's integrated waste processing business has developed well according to the installed capacity of Biourine A Plus and In-site Trychocompose (ITC) production. The implementation of activities is broadly in line with the target. The achievement of ITC production has been 56% of installed capacity but seen from the production trend has shown the direction towards actual capacity use. The income of group business has a significant increase that almost double. The constraints faced are mainly caused by fluctuations in the supply of the main raw materials (liquid waste and solid cages) as the cattle population changes. Follow-up efforts are to encourage changes in business orientation into a dual purpose: to maintain the balance of composition between male and female livestock, and expansion of partnerships of raw material input with the aim of non-group cattle farmers.